Fracture prediction of circular steel tubular X-joints using a Lode parameter enhanced cyclic void growth model. (15th October 2021) - Huang, Xuewei; Wei, Chenchen; Zhao, Jun; Zhao, Wei; Ge, Jianzhou
Highlights: A Lode parameter enhanced cyclic void growth model was proposed. Monotonic and ELCF loading tests were conducted on various stress state of steel. The mechanical properties of X-joints under different loading histories were compared. Fracture failure of X-joints under monotonic loading and ELCF loading was simulated. The LCVGM shows better performance than the CVGM in fracture prediction of X-joints. Abstract: The extremely low cycle fatigue failure of steel tubular joints under strong seismic action may lead to progressive collapse of the structures. The prediction models of extremely low cycle fatigue fracture focused on the tensile fracture models and often ignored the influence of shear effect. Within the scope of fracture model based on microscopic mechanism, a Lode parameter enhanced cyclic void growth model (LCVGM) was proposed by improving the cyclic void growth model (CVGM) in the study. The LCVGM can comprehensively consider stress triaxiality sensitivity and Lode parameter dependence in extremely low cycle fatigue fracture prediction. The monotonic tensile and extremely low cycle fatigue tests were conducted on the different types of base metal and weld metal specimens in circular steel tubular joints. The micro fracture morphology of the specimens was observed by scanning electron microscope, and the fracture properties of both materials were compared. Moreover, LCVGM parameters of base metal and weld metal were calibrated, and the model was validated against extremely low cycle fatigue tests results of plate specimens. The fracture failure tests of circular steel tubular X-joints under monotonic loading and extremely low cyclic loading were completed. The joints exhibit chord punching failure mode. Finally, the numerical simulations of fracture tests of the joints were performed by means of the LCVGM and CVGM. The analysis results demonstrate that the fatigue life predicted by LCVGM is consistent with the test results, while the predicted life obtained from CVGM is significantly longer than the test result due to neglecting the influence of shear effect.